Theodor Heuss, Privatier und Elder Statesman - Heuss, Theodor (Briefe, 2014)
After his time in office as Federal President came to an end, one would hardly describe Theodor Heuss as living a life of retirement. He traveled, wrote books and articles, voiced his opinions on political and social issues in lectures, and not least, was an indefatigable correspondent. During the last four years of his life, Heuss remained a sought&#8211after figure in public life whose opinions drew wide attention in Germany and abroad.